Identifikasi Faktor-faktor Kerukunan dalam Masyarakat Multietnis - Nhadya Almar Putri; Eka N. Kencana; Ketut Jayanegara (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The development of ethnic diversity in Indonesia poses challenges in social interactions. This study aims to identify the factors influencing inter-ethnic harmony in the Jalan Gajah Mada area, Denpasar. Using a qualitative approach, data were obtained through observations and interviews. The results show that intense inter-ethnic interactions support cultural acculturation, reduce conflicts, and enhance harmony. Factors such as tolerance, cultural exchange, and economic harmonization play crucial roles in creating a harmonious environment. In conclusion, understanding these factors is important for maintaining progress and harmony in multi-ethnic areas like Jalan Gajah Mada, Denpasar, and can be applied in other regions facing similar conflicts. The research findings indicate two factors in each dimension, with the general cooperation factor being the most dominant at 49.176%, followed by non-religious tolerance at 42.351%, freedom of religion at 41.858%, support for inter-ethnic humanitarianism at 26.290%, inter-ethnic cooperation at 20.838%, and finally inter-religious tolerance at 20.107%.